2008
DOI: 10.1111/j.1539-6924.2008.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregating Disparate Epidemiological Evidence: Comparing Two Seminal EMF Reviews

Abstract: Two seminal reviews (IARC, 2002; CDHS, 2002) of possible health effects from power-frequency EMFs reached partly different conclusions from similar epidemiological evidence. These differences have an impact on precautionary policy. We examine the statistical aggregation of results from individual disparate studies. Without consistent exposure metrics, the advantage of meta-analysis to estimate magnitude of effect is lost. However, counting positive and statistically significant results yields important informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The findings of the California Department of Health Services (CDHS) in its 2002 report conclude that EMF can cause some degree of increased risk of childhood leukaemia and adult brain cancer but, in contrast, they also affirm that EMF do not increase the risk of birth defects, breast cancer, heart disease, Alzheimer's disease or depression (Neutra et al 2002). Recently, a comparison between two seminal reviews, from the International Agency for Research of Cancer (IARC) and CDHS, about possible health effects of EMF has been reported reaching partly different conclusions from a similar epidemiological study (O'Carroll and Henshaw 2008). These authors found that there was indeed evidence of association between MF exposure and increased risk of adult leukaemia and adult brain cancer, but the appropriate analysis was not carried out in the IARC Report.…”
Section: Introductionmentioning
confidence: 96%
“…The findings of the California Department of Health Services (CDHS) in its 2002 report conclude that EMF can cause some degree of increased risk of childhood leukaemia and adult brain cancer but, in contrast, they also affirm that EMF do not increase the risk of birth defects, breast cancer, heart disease, Alzheimer's disease or depression (Neutra et al 2002). Recently, a comparison between two seminal reviews, from the International Agency for Research of Cancer (IARC) and CDHS, about possible health effects of EMF has been reported reaching partly different conclusions from a similar epidemiological study (O'Carroll and Henshaw 2008). These authors found that there was indeed evidence of association between MF exposure and increased risk of adult leukaemia and adult brain cancer, but the appropriate analysis was not carried out in the IARC Report.…”
Section: Introductionmentioning
confidence: 96%
“…Electromagnetic fields (EMFs) emanating from man-made electrical devices, such as mobile phones, powerlines, and radar, are ubiquitous in the environment. Associations have been reported between brain cancer and chronic exposure to environmental EMFs (Berg et al, 2006;Villeneuve et al, 2002), but there is no agreement on the scope and extent of the risk to public health (O'Carroll and Henshaw, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide concerns about the potential health risks of ELF‐MF have provoked increasing scientific interest and become an issue of great public debate. Many studies have reported an association between ELF‐MF exposure and human health, with emphasis on a variety of clinical diseases, including: brain tumors, colon cancer, breast cancer, acute childhood leukemia, genotoxicity, neurodegenerative diseases, infertility, birth defects, increased risk of miscarriage, and others [Ahlbom et al, ; Kundi et al, ; Garcia et al, ; Kheifets et al, ; O'Carroll and Henshaw, ; Davanipour and Sobel, ; Huss et al, ; Gharagozloo and Aitken, ]. Because of the high sensitivity of male reproductive organs to environmental hazards and the problems of declining sperm quality and infertility, considerable attention has been focused on the potential risk of ELF‐MF to male reproduction.…”
Section: Introductionmentioning
confidence: 99%